Analysis of a latent heat thermal energy storage unit with metal foam insert in both the HTF and PCM sides. (October 2019) - Chen, X; Xia, X L; Wang, F Q; Sun, C; Liu, R Q
Abstract: Latent heat thermal energy storage (LHTES) systems using phase change material (PCM) have received significant research attention in numerous engineering fields. The transient heat transfer phenomenon inside a vertical LHTES unit is numerically investigated, with the paraffin as the PCM and water as the heat transfer fluid (HTF). As a performance enhancement technique, the metal foam insert is applied in both the HTF and PCM sides. The conjugate thermal model for the HTF/foam-wall-PCM/foam system is built, considering the non-equilibrium effect between the solid and fluid phases with two-temperature energy equation and the natural convection inside the PCM with Boussinesq approximation. The enthalpy-based method is employed to account for the solid-liquid phase change problem. The overall performance is compared with other three cases: no foam insert, foam insert in HTF side and foam insert in PCM side. Besides, parametric study is also conducted on the melting features, including the foam structural parameters and inlet conditions of HTF. The results show that foam insert in both sides accelerates the PCM melting effectively. The foam porosity and HTF inlet temperature play important roles in the overall heat transfer, whereas the pore density and HTF inlet velocity have limited effects on the melting rate. The findings can provide referential information for the design of a LHTES system.